2019
DOI: 10.1126/sciadv.aax6061
|View full text |Cite
|
Sign up to set email alerts
|

A new metal transfer process for van der Waals contacts to vertical Schottky-junction transition metal dichalcogenide photovoltaics

Abstract: Two-dimensional transition metal dichalcogenides are promising candidates for ultrathin optoelectronic devices due to their high absorption coefficients and intrinsically passivated surfaces. To maintain these near-perfect surfaces, recent research has focused on fabricating contacts that limit Fermi-level pinning at the metal-semiconductor interface. Here, we develop a new, simple procedure for transferring metal contacts that does not require aligned lithography. Using this technique, we fabricate vertical S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
102
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(114 citation statements)
references
References 47 publications
7
102
0
Order By: Relevance
“…This ratio of in-plane to out-of-plane minority carrier diffusion lengths is significantly larger than reported values for n-WSe 2 generated through traditional, bulk photoelectrochemical experiments, 63 which may be attributable to the degree to which the experimental geometry is defined and the influence of defects can be controlled in the CG-TC SECCM experiments presented here. This value is, however, consistent with the broader range of studies of carrier transport in TMD materials, where mobility ratios up to ~10 7 have been reported. [63][64][65][66][67][68]…”
Section: Please Do Not Adjust Marginssupporting
confidence: 91%
See 1 more Smart Citation
“…This ratio of in-plane to out-of-plane minority carrier diffusion lengths is significantly larger than reported values for n-WSe 2 generated through traditional, bulk photoelectrochemical experiments, 63 which may be attributable to the degree to which the experimental geometry is defined and the influence of defects can be controlled in the CG-TC SECCM experiments presented here. This value is, however, consistent with the broader range of studies of carrier transport in TMD materials, where mobility ratios up to ~10 7 have been reported. [63][64][65][66][67][68]…”
Section: Please Do Not Adjust Marginssupporting
confidence: 91%
“…The unique optoelectronic properties of two-dimensional semiconductors (2DSCs), such as the transition metal dichalcogenides (TMDs), make them attractive candidates for use in a variety of electronic and photonic devices, including photovoltaic cells, [1][2][3][4][5][6][7] photodetectors, [8][9][10] and LEDs. 11,12 The inherent 2D structure of these materials allows them to be prepared as ultrathin films down to the monolayer limit, which can serve as flexible active layers with favorable optical properties as compared to the bulk material.…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of recent reports unambiguously demonstrated that OSCs based on TMDs, such as sulfides and selenides as HTLs and/or ETLs, exhibited superior performance, in terms of both PCE and stability, compared with other used materials. [310,312,313] Representative examples are discussed in this section.…”
Section: Transition Metal Dichalcogenides (Tmds)mentioning
confidence: 99%
“…E, Simulated I ‐ V characteristics of the fully optimized WS 2 device. C‐E, Reproduced with permission from Reference 218. F, Schematic illustration of the vertical WSe 2 /MoS 2 device with the WO x layer.…”
Section: Synthesized Tmdcs For Optoelectronicsmentioning
confidence: 99%